Prinsip Kehati-Hatian Notaris di Era Digital: Implementasi dalam mewujudkan Akta yang Sempurna - Rostarum, Triamy (Universitas Batanghari Jambi, 2024)
This research examines the challenges faced by notaries in the digital age and the significance of the principle of caution in creating authentic deeds. The digital transformation has significantly altered the notary profession, introducing new risks such as identity fraud. The principle of caution has become increasingly crucial to ensure the integrity and validity of deeds. This study analyzes various forms of caution that notaries should adopt and their impact on the quality of authentic deeds. Findings indicate that adapting to digital technology and a deep understanding of the principle of caution are key for notaries to navigate the challenges of the modern era.